1972
DOI: 10.1246/bcsj.45.1709
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Studies and Analytical Applications of Vanadium(IV) Chelates with 4-(2-Pyridylazo)resorcinol and 1-(2-Pyridylazo)-2-naphthol

Abstract: Oxovanadium(IV), VO2+, gives sensitive colour reactions with 4-(2-pyridylazo)resorcinol (ε=2.54×104 at λmax 550 nm) and 1-(2-pyridylazo)-2-naphthol (ε=1.02×104 at λmax 560 nm). The composition of the complexes VO2+: PAN or PAR was established by the continuous variations, mole ratio, and Asmus straight line methods. Lambert-Beer’s law range, Ringbom optimum range, pH stability range, photometric error, and stability constant values were also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Such an oxidation has been observed in other V(IV)-PAR containing systems; [29][30][31] it could be avoided if special precautions are taken: inert atmosphere, 30 low temperature and flushing the solutions with nitrogen. 32 Our present investigations on the vanadium(IV)-PAR-TNBT-water-chloroform system showed that the optimum pH range for extraction of V(IV) is pH = 4.0 to 4.9 ( Figure 3, curve 4), λ max appears at 560 nm (Figure 2, curve 4), and both the molar ratios PAR:V(IV) and TNBT:V(IV) are 2:1. Having in mind the state of V(IV) 33 and PAR 28,34 at the optimum acidity, and the literature 23 we suggest the following scheme of complex formation:…”
Section: Vanadium(iv)-par-mbt-water-chloroform Systemsmentioning
confidence: 59%
See 1 more Smart Citation
“…Such an oxidation has been observed in other V(IV)-PAR containing systems; [29][30][31] it could be avoided if special precautions are taken: inert atmosphere, 30 low temperature and flushing the solutions with nitrogen. 32 Our present investigations on the vanadium(IV)-PAR-TNBT-water-chloroform system showed that the optimum pH range for extraction of V(IV) is pH = 4.0 to 4.9 ( Figure 3, curve 4), λ max appears at 560 nm (Figure 2, curve 4), and both the molar ratios PAR:V(IV) and TNBT:V(IV) are 2:1. Having in mind the state of V(IV) 33 and PAR 28,34 at the optimum acidity, and the literature 23 we suggest the following scheme of complex formation:…”
Section: Vanadium(iv)-par-mbt-water-chloroform Systemsmentioning
confidence: 59%
“…It should be mentioned that the stability of [Chel] n-in ternary tetrazolim IACs with participation of ADR is sometimes unknown due to the fact that T m+ (in particular MBT 2+ ) could stabilize different anionic species (e.g. with 2:1 ADR/V ratio 10,[20][21][22][23][24]39 ) in comparison to these obtained in aqueous solutions 29,30,32,35 or by extraction with other heavy organic salts. 34,[40][41][42] …”
mentioning
confidence: 99%
“…At pH values higher than 3.2 -3.5 (if C V(IV) is in the interval from 10 -5 mol L -1 to 10 -4 mol L -1 ) a neutral V(IV)-form VO(OH) 2 prevails [39]. This form can be stable up to pH 6.3-6.4 [39], provided that precautions are taken to avoid aerial oxidation of V(IV) [37,40].…”
Section: It Is Known That Vo 2+ ([Vo(h 2 O) 5 ]mentioning
confidence: 99%
“…In the interpretation of the obtained experimental results, we used information for the complex formation between V IV and ADs in the presence [32][33][34][35] or absence [23,[35][36][37][38] of auxiliary reagents. We suggested several structures of the chromogenic anionic part of the extracted species.…”
Section: Introductionmentioning
confidence: 99%